The The public sphere between the Aufklärung and antagonism - the priority of Kant’s social philosophy in his reflections on history - Santos, Bernardo (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In this work I seek to explain the relationship between the substantially different characterizations of the public sphere made by Kant. In his writings on the Enlightenment, the productive component of this space is emphasized and the conditions that allow social and political progress to be fostered are identified. On the other hand, in the texts on the idea of a universal history, its antagonistic dynamics are rather emphasized. At first glance, the teleological history according to a plan of nature seems to relegate the public sphere and the public use of reason to a secondary role. However, given the epistemic status of the philosophy of history, I will seek to highlight that, on the contrary, this regulative idea only has philosophical significance due to the effects of its public dissemination. Thus, what motivated the elaboration of a philosophy of history was rather the political potential of public thought, and, thus, the teleology of history is secondary to the conception of the public sphere.